Joyce the Postmodernist: A Glance at Finnegans Wake - Zangouei, Javad (k@ta: A Biannual Publication on the Study of Language and Literature, 2013)
Postmodernism criticizes metanarratives. Modern metanarratives including Enlightenment, Hegelianism, and Marxism present general claims about knowledge and truth. Under postmodern condition metanarratives are damageable, criticizable, and finally negligible. In this essay metanarratives are explained and the incredulity towards them is traced. In Finnegans Wake, which is under postmodern condition, metanarratives are targets of Joyce’s parody. In this novel, religion is bitterly criticized, Enlightenment is mocked, and Hegelianism and Marxism are disfigured. Joyce shows his incredulity towards metanarratives and employs postmodernist techniques. Finnegans Wake’s world is postmodern.